A pioneer in the study of funerary art in Brazil: interview with Maria Elizia Borges (TEL Tempo, Espaço e Linguagem, 2025)
Interview granted to the organizers of the Dossier “In life, death, I know you”: interdisciplinary perspectives on contemporary finitude (20th-21st centuries)." The ambiguity that marks our relationship with the phenomenon of death is more evident than ever, thanks to technologies that now connect us globally, in real time. Misunderstood, silenced or feared when it comes to the personal experience of the final moment, for which there are no absolute answers, death reinforces social bonds, guides actions in the present and the look at the past, and moves the imagination regarding the possibilities of what will (or will not) be for the living and those who “departed”. Dissociated from this experience, it becomes an object of consumption that circulates almost unfiltered through streaming channels, stores and social networks today, enabling new approaches, from the most creative to those that seem to empty death of meanings. cemetery and funerary art studies, which is why we invited her for this interview.